Ways of Effective School Management: The Role of School Principals in Building of Quality and Effective School - Mammadzada, Mirali (International Journal of Sciences: Basic and Applied Research (IJSBAR), 2021)
Effective school management is an important responsibility for principals around the globe, for this purpose different organizations create workshops, responsibility divisions, and training programs to be able to maintain a well-organized environment. Among the many opinions regarding the role of school principals, few can argue that they are the driving force behind the most effective and academically rigorous schools in the country. School principals need to be financially responsible too, and in order to be successful in this area, it is critical to have the support of parents, students, and the community. School management productively becomes a support for creating a generation of high achievers and for the implementation of a school culture that adapts to society's needs. Principals who understand the challenges associated with leadership are more likely to build excellent school culture. This paper aims to contribute experience and ideas of effective school management, not only for the principal but also for the school's improvement and effectiveness. It will also explore the nature and essence of effective school management. This study will follow a quantitative research methodology; the literature review will discuss the factors affecting school management and the role of the principal in this regard. This study will help other researchers to understand the issues related to school management and the effectiveness of principals as leaders. This study further aims to examine whether the principals' emotional intelligence makes them more effective transformational leaders (specifically, their ability to recognize emotional states in others), as demonstrated by how emotions are framed. For the research purpose, a total of 69 randomly selected primary school's data were analyzed for their principals and teachers. The principals took part in a performance task that assesses their ability to identify and communicate emotions. Among the teachers' samples, half reported on principal leadership behaviors. In contrast, others commented on teachers' subjective perceptions of principals, as displaying leadership behaviors that reinforce teachers' reframing of unfavorable emotions into more positive ones. Teachers' emotional reframing, and principals' ability to recognize emotions, were associated with principals' transformational leadership behaviors [1].